APPLICATION OF SYSTEMATIC APPROACH IN THE PROCESS OF FORMING THE READINESS OF AFU FUTURE OFFICERS FOR PROFESSIONAL ACTIVITY: THEORY AND PRACTICE - Ryzhykov, V.; Didenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article discusses the use of the system approach of future officers training in higher military educational institutions, analyzes the basic principles of the pedagogical system, which are defined by the system as a holistic organized set of military training, which ensures stable behavior and effective results of military education. The basic systems of professional training in higher military educational institutions, which have the conditional level of involvement in the educational process, are revealed. However, the basis is the inalienability of all systems in the training of future officers of the Armed Forces, and the interchangeability or absence of any training system leads to irreparable consequences, the result of which is not fully formed professional readiness of an officer of the Armed Forces. Theoretically, professional readiness is formed as knowledge, skills and competencies fully acquired, but the important point remains whether psychological professional readiness is formed during the extreme situation of military service. In view of the material presented in the scientific article, the conclusion is that the training of officers of the Armed Forces in higher military educational institutions is a system one. The result of the training process of future officers in higher military educational institutions is a high level of cadets readiness for practical activities, which can be achieved only by streamlining the system on the basis of certain principles to which we include: the principle of objectivity, completeness, specific historical (genetic) approach, systematics, contradictions of pedagogical experience. This makes it possible to organize the specific functioning of all subsystems of future officers training and their effective interaction in accordance with the aspect and general goals and objectives. When modeling the system approach of professional training in higher military educational institutions the main pedagogical systems (types of training) involved in the training of officers of the Armed Forces are used. Each of them has its purpose and objectives, specific content, means and methods. Because the professional training of future officers of the Armed Forces is an integration process of formation of the same five basic systems (theoretical, psychological, physical, training and practical (officer training in combat units)).
Keywords: system approach, professional training, military professional readiness, pedagogical systems